Collaborative Planning on Cross-Border Service of Water Supply in Surakarta Urban Border Area, Indonesia - Hadi Wahyono; Achmad Djunaedi; Bakti Setiawan; Leksono Subanu (Department of Urban and Regional Planning, Universitas Diponegoro, 2014)
Recently, many planners apply collaborative planning theory in planning involving two or more parties, such as between government, private and community, including in the interregion cooperation. However, the theory has rarely been used to explain the interaction between regions in city border area, especially in the cases in Indonesia. This article discusses the case of cross-border service of water supply of the Local Water Company (PDAM-Perusahaan Daerah Air Minum) of Surakarta City into the urban border area of Sukoharjo Regency, based on collaborative planning theory. This article is written based on results of the research on the case using case study research method. The discussion concludes that the approach of collaborative planning theory used on the case is cooperative-accommodation approach. It is because PDAM of Surakarta City accommodate the cross-border region service as a reciprocal policy, as most of their water inputs come from their neighboring regions. In general, such an approach is in accordance with the need of the interacting regions, which one region needs supporting service to meet the need of their communities in water service, and another can fulfill the need based on its capacity. In this case, the concerned technical agencies, PDAM of every region interact each other directly in providing the service. The important thing, the interaction is in line with the prevailing cross-border region bureaucratic regulations and does not infringe the autonomy of every region.